Dental manifestations in Ehlers Danlos syndrome (EDS) - Report of a case - Shobha R Hiremath; Surekha Puranik; Mangala Meti; D.N.S.V Ramesh (Wolters Kluwer Medknow Publications, 2007)
Ehlers Danlos Syndrome (EDS) is an unusual disease entity afflicting many body systems. It is a hereditary disorder of the connective tissue. Dental manifestations are described. Attention is drawn to the role of the dentist in diagnosing a generalized disorder.